2018
DOI: 10.1249/mss.0000000000001643
|View full text |Cite
|
Sign up to set email alerts
|

Heat Loss Is Impaired in Older Men on the Day after Prolonged Work in the Heat

Abstract: Prolonged work in the heat causes next-day impairments in whole-body heat loss, which exacerbate heat storage and may elevate the risk of heat-injury on the following day in older workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…Consistent with our recent work [4], we observed impaired WB-NHL (Figure 1(c)) primarily due to reduced evaporative heat loss on day 2 relative to day 1 (Figure 1(a)). Reductions in WB-NHL were also observed across days 2-5 (Figure 1(c)).…”
Section: Front Matter: Discoverysupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with our recent work [4], we observed impaired WB-NHL (Figure 1(c)) primarily due to reduced evaporative heat loss on day 2 relative to day 1 (Figure 1(a)). Reductions in WB-NHL were also observed across days 2-5 (Figure 1(c)).…”
Section: Front Matter: Discoverysupporting
confidence: 92%
“…In our recent work [4], we tested the hypothesis that those next-day rises in core temperature in middle-aged workers may be partly ascribed to reduced whole-body net heat loss (evaporative heat lossdry heat gain; WB-NHL). Using direct calorimetry, we assessed time-dependent changes in WB-NHL in men aged 53-64 years during heat stress tests involving exercise at increasing, fixed rates of metabolic heat production (150, 200 and 250 W m −2 ) in hot, dry conditions.…”
Section: Front Matter: Discoverymentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, in young adults, previous research reported no impairment of heat loss and no additional heat storage on the day after performing 7.5 h of fixed-paced physical work in hot dry conditions (Notley et al 2018b). However, impairments in heat loss on day two vs day one were found in older adults completing a similar protocol (Notley et al 2018a). These observations are of particular relevance as they indicate that our current findings may reasonably translate to settings in which extended work is performed on multiple successive days (i.e.…”
Section: Discussionmentioning
confidence: 99%